2005
DOI: 10.1007/s00520-005-0792-9
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of povidone-iodine and normal saline mouthwashes on oral mucositis in patients after high-dose chemotherapy and APBSCT—results of a randomized multicentre study

Abstract: Antimicrobial solutions are widely used in the nursing care of chemotherapy induced oral mucositis (OM). There is little evidence, however, supporting their use for reducing mucosal damage. In our study, 132 patients were randomized to use normal saline (n=65) or povidone-iodine diluted 1:100 (n=67) mouthwashes for OM prophylaxis and treatment after high-dose chemotherapy comprising BEAM or HD-L-PAM followed by autologous peripheral stem cell transplantation. The study groups were well balanced in respect of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 12 publications
2
37
1
2
Order By: Relevance
“…It was found that the subjects receiving this special oral hygiene regimen had a significantly lower incidence of OM as compared to a control group which consisted of basic toothbrushing on their own (n=20 in each group) [85]. On the other hand, a multicenter RCT with 132 HSCT patients found no difference between mouth rinsing with povidone-iodine or saline in OM, fever of unknown origin, or other infections [82]. No guideline was possible due to insufficient and conflicting evidence.…”
Section: Povidone-iodinementioning
confidence: 99%
“…It was found that the subjects receiving this special oral hygiene regimen had a significantly lower incidence of OM as compared to a control group which consisted of basic toothbrushing on their own (n=20 in each group) [85]. On the other hand, a multicenter RCT with 132 HSCT patients found no difference between mouth rinsing with povidone-iodine or saline in OM, fever of unknown origin, or other infections [82]. No guideline was possible due to insufficient and conflicting evidence.…”
Section: Povidone-iodinementioning
confidence: 99%
“…A number of publications focused on oral antiseptics but their conclusions are equivocal. For example Vokurka et al 5 found no difference between the use of iodide preparations as oral antiseptics and saline. The product, Listerine (Pfizer) we used is an antiseptic agent containing essential oils (thymol, eucalyptol, menthol, methyl salicylate) and alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies [4,25,26,32,39,44,63,66,69] were located that examined the effects of normal saline mouthwash on prevention of OM across a variety of treatment populations. Levels of evidence varied and results were conflicting.…”
Section: Normal Saline Mouthwashmentioning
confidence: 99%